Left ventricular hypertrophy. Relation of structure to diastolic function in hypertension. - Shapiro, L M (1984)
Digitised M mode echocardiography was used to determine the relation between the degree of left ventricular hypertrophy and abnormalities of isovolumic relaxation and diastolic function. Fifty six patients with varying severity of non-malignant systemic hypertension without evidence of ischaemic heart disease, left ventricular dilation, or clinical heart failure were studied. In addition, 10 athletes with hypertrophy and 20 normal subjects were studied. Athletes and patients with moderate (systolic blood pressure 175 to 200 mm Hg) and severe hypertension (greater than 200 mm Hg) had a significant increase in left ventricular mass. Cavity dimensions were normal in hypertensive patients and increased in athletes. Systolic function was normal in all groups. Regardless of the degree of hypertrophy patients with hypertension had a prolonged isovolumic relaxation period and delayed mitral valve opening. Patients with hypertrophy also had a reduced rate and prolonged duration of rapid early diastolic dimension increase and posterior wall thinning. Athletes, however, who had an equivalent degree of hypertrophy to patients with moderate or severe hypertension had entirely normal function. Measurements of diastolic function were significantly correlated with wall thickness and left ventricular mass. These indices of hypertrophy, particularly posterior wall thickness and the sum of posterior wall and septal thickness, were positively correlated with the duration of isovolumic relaxation and delay in mitral opening and negatively with the peak rate of early diastolic dimension increase and wall thinning. Thus in hypertensive patients with non-dilated left ventricular hypertrophy there appears to be a relation between the degree of wall thickening and abnormalities of diastolic function.